ANALISIS POLA DAN BENTUK-BENTUK KOMUNIKASI PEMBELAJARAN BERBASIS ONLINE LEARNING (STUDI KASUS PADA MAHASISWA UNIVERSITAS TERBUKA KOTA BATAM) - Febriadi Situmorang Situmorang; Michael Jibrael Rorong (LPPM Universitas Putera Batam, 2026)
In the digital era and with the advancement of information technology, learning through online platforms has become increasingly significant in the field of education. Online learning offers flexibility, broader access to educational resources, and more varied interactions. However, the effectiveness of online learning is often influenced by the communication patterns used in the process. This study aims to analyze the communication patterns and forms in online-based learning at Universitas Terbuka (UT), a distance education institution in Indonesia. UT provides access to higher education for individuals who face challenges accessing formal education in conventional universities due to various constraints such as geographical location, employment, or time limitations. The method used in this study is a qualitative-descriptive approach, with in-depth interviews and observations as the primary data collection techniques. The results indicate that the communication patterns implemented at UT are dominated by Computer Mediated Communication (CMC), involving the use of e-learning platforms for asynchronous and synchronous communication. These findings suggest that the use of CMC at UT not only facilitates flexible and responsive interactions but also supports the continuity of the teaching and learning process in a distance education environment.